Electronic commerce and the attitude towards tax evasion of companies, Province of San Martin, 2021 - Enrique (2022)
The research presented seeks to determine the relationship of electronic commerce in tax evasion of service companies in the province of San Martín, it was considered an investigation with a quantitative approach, with a non-experimental design and correlational scope, where the survey was used as a technique. and the instrument the questionnaire, to determine the level of reliability of the present investigation, the Cronbach's alpha statistic was used. For data collection, a sample of 30 service companies was considered using inclusion and exclusion criteria, which allowed knowing the behavior of the variables. Whose information collected in the questionnaire, the results were processed through the SPSS program where the analysis and reliability were carried out, between the variable electronic commerce and tax evasion, according to the Spearman's Rho test, from which a correlational result of 0.844 was obtained. in which the result establishes a strong relationship and reaching the conclusion that electronic commerce affects tax evasion of service companies in the province of San Martín.